Sistem Informasi Administrasi Puskesmas Berbasis Multi User - Iwan Koerniawan; Rahayu Nugraheni Rachmawati; Widi Utomo (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
The Mranggen III Health Center is one of the government agencies in the technical implementing unit of the Demak District health office. Patient registration services and administrative payments at the Mranggen III Health Center are still conventional, causing long queues. In addition, the process of processing data to become information cannot be accessed directly by the leadership because there are no computerized and multi-user or client-server applications. Based on these problems, a Puskesmas administration information system design was made that could suit the needs. Making an information system using the programming language Microsoft Visual Basic 6.0 and SQL Server 2000 as a multiuser-based database. With the design of the development of an administrative information system for the Mranggen III Health Center, it is hoped that it will be able to handle the problems that exist in the Mranggen III Health Center, namely being able to speed up service to patients and by using a multiuser-based information system. Leaders and several staff can access it simultaneously and quickly.